Turbulent filament properties in L and H-mode regime in the RFX-mod operating as a tokamak. (23rd September 2020) - Grenfell, G.; Spolaore, M.; Abate, D.; Carraro, L.; Marrelli, L.; Predebon, I.; Spagnolo, S.; Veranda, M.; Agostini, M.; van Milligen, B.Ph.; Cavazzana, R.; Cordaro, L.; et al.
Abstract: The dynamics of turbulent filaments in L and ELM-free H-mode in the RFX-mod device operating as a tokamak is discussed in the present work. L-H transition and sustained H-mode have been achieved in the RFX-mod with the aid of an external electrode biasing (Spolaore et al 2017 Nucl. Fusion 57 116039). Through advanced statistical techniques, turbulent filaments are detected and tracked from the edge to the scrape-off layer (SOL) in a two-dimension floating potential map (measured with a 2D array of Langmuir probes) related with extreme events of a fixed ion saturation current signal in the SOL. While in L-mode filaments travel almost freely, their motion becomes restricted to the near SOL during the induced biasing H-mode. In this region, the background shear decorrelation time becomes shorter than the convective filament time, favouring its suppression. However, the experimental observation of a nearly 'trapped' monopole potential points out the possible role of the vortex selection mechanism. The sign and magnitude of the turbulent parallel vorticity are consistent with the E × B background vorticity in the SOL in this regime, while in L-mode, the inferred turbulent vorticity is always above the background one. The sparse filamentary transport in the far SOL during H-mode is further confirmed from the measurements of a poloidally symmetric array of electrostatic sensors on the wall. Lastly, the radial velocity of filaments in both regimes was discussed in the framework of analytical scalings. Filaments in L-mode exhibit a reasonable agreement with the sheath-limited regime in the cold ion approximation, with a non-negligible associated parallel current density measured with a set of 3-axial pick-up coils installed in the probe head. In H-mode, the collisionality increases near the separatrix while filaments seem to follow the inertial regime before become trapped.